A new approach to improving the estimate of Delta () under European option - Mehrdoust, Farshid (International Journal of Applied Mathematical Research, 2012)
Estimating option sensitivities is another quite important task in nancial mathematics. In this paper, we improve the estimate of value for a vanilla European option by a robust stochastic algorithm based on quasi Monte Carlo methods and the antithetic variance reduction technique. In comparison to existing the naive Monte Carlo methods, we can improve accurate signi cantly by implementing our proposed algorithm.